2000
DOI: 10.1121/1.429413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of speaking rate and contrastive stress on formant dynamics and vowel perception

Abstract: Vowel formants play an important role in speech theories and applications; however, the same formant values measured for the steady-state part of a vowel can correspond to different vowel categories. Experimental evidence indicates that dynamic information can also contribute to vowel characterization. Hence, dynamically modeling formant transitions may lead to quantitatively testable predictions in vowel categorization. Because the articulatory strategy used to manage different speaking rates and contrastive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Furui ͑1986͒, in a series of experiments, showed that speech segments of 10 ms, excised at the point of maximum spectral change, contain the most important information for identification of consonant-vowel transitions. In spite of the perceptual importance of vowel dynamics, Watson andHarrington ͑1999͒ andPitermann ͑2000͒ reported no improvements in automatic vowel classification when dynamic parameters were added to static features. Watson and Harrington ͑1999͒ argued that dynamic information, such as spectral rate of change, may be related to prosodic aspects of vowels rather than carrying phonetic information.…”
Section: Introductionmentioning
confidence: 87%
“…Furui ͑1986͒, in a series of experiments, showed that speech segments of 10 ms, excised at the point of maximum spectral change, contain the most important information for identification of consonant-vowel transitions. In spite of the perceptual importance of vowel dynamics, Watson andHarrington ͑1999͒ andPitermann ͑2000͒ reported no improvements in automatic vowel classification when dynamic parameters were added to static features. Watson and Harrington ͑1999͒ argued that dynamic information, such as spectral rate of change, may be related to prosodic aspects of vowels rather than carrying phonetic information.…”
Section: Introductionmentioning
confidence: 87%
“…Despite the preceding discussion, which suggests that acoustic effects of rate change may be small (relative to kinematic variability), studies of the acoustic effects of speaking rate change have identified a variety of speaker and context-related effects on formants (Agwuele, Sussman, & Lindblom, 2008;Fourakis, 1991;Gay, 1968Gay, , 1978Hertrich & Ackermann, 1995;Lindblom, 1963;Pitermann, 2000;Rosen et al, 2011;Tjaden & Weismer, 1998;van Son & Pols, 1992;Weismer & Berry, 2003). Taken together, these studies indicate a wide range of possible speaker-specific and context-related effects of speaking rate change.…”
Section: Acoustic Effects Of Speaking Rate Changementioning
confidence: 80%
“…Indeed, if reduction is too strong, the recovery may fail (see e.g. Pitermann, 2000). Moreover, if recovery were complete, automatic and effortless, there would be no need (1) The listener is able to process current height and duration in order to separately recover the intended height control (vowel reduction) 1 and the intended vowel duration; (2) Recovery is constrained by both articulatory knowledge and auditory processing, as shown by the organization of sound systems in human languages.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, if reduction is too strong, the recovery may fail (see e.g. Pitermann, 2000). Moreover, if recovery were complete, automatic and effortless, there would be no need for a speaker to hyperarticulate, while the control of articulatory strength is obviously part of the speaker's program (see Moon & Lindblom, 1994).…”
Section: Resultsmentioning
confidence: 99%